The effect of concurrent androgen deprivation and 3D conformal radiotherapy on prostate volume and clinical organ doses during treatment for prostate cancer - Onal, C (The British Institute of Radiology., 2009)
In this study, we investigated the shrinking effect of concurrent three-dimensional conformal radiotherapy (3D-CRT) and androgen deprivation (AD) on prostate volume, and its possible impact on the dose received by the rectum and bladder during the course of 3D-CRT. The difference between the prostatic volumes determined on pre-treatment planning CT (PL-CT) and post-treatment CT (PT-CT) following a 3D-CRT course was assessed in 52 patients with localised prostate carcinoma. The changes in mean prostate volume when compared with PL-CT and PT-CT-based measurements were assessed. The pre- and post-treatment mean prostate volumes for the whole study population were 49.7 cm(3) and 41.0 cm(3) (p _ 0.02), respectively. The study cohort was divided into two groups depending on the duration of neoadjuvant androgen deprivation (NAD): 23 patients (44.7%) were designated as “short NAD” (≤3 months; SNAD) and the remaining 29 (55.3%) as “long NAD” (>3 months; LNAD). Patients on SNAD experienced a significantly greater reduction in prostate volume compared with those on LNAD (14.1% vs 5.1%; p _ 0.03). A significant increase in rectum V(40–60) values in PT-CT compared with PL-CT was demonstrated. LNAD patients had significantly higher rectal V(50–70) values at PT-CT compared with the SNAD group. There was a significant decline in V(30)–V(75) bladder values in PT-CT compared with PL-CT in the SNAD group. In conclusion, a higher prostate volume reduction during 3D-CRT was demonstrated when RT planning was performed within 3 months of NAD. However, this reduction and daily organ motion may lead to an unpredictable increase in rectal doses.